(3LRA ef NWHI MGOi GdCQhGM Edi HdGO GdCaQGMs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3CeG HYO aEf Gddg JYGdi de jNdb Ndbg YHKkG Hd Ndbge dCeQ YXje s
(3BNQgG (B:s
(3efGHQ ef fhQ gfGc heVg aEf cfJ dGJOQi aJdc eUjHg hEf cfJ JOQi aGdeUjHI CYXe EfJgJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3hQO ai cTa GdXfhf L(B1 (3U (B623 (3Cf MGOi GdCQhGM Edi HdGO GdCaQGM (B/ (3gh dTeS GdOjf eMeO Hf Gdbje GdLhRjI GdeJhai SfI (B751(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
(3eUOQ GbJfGA GdCUd (B:s
(3eLGejY s
Keywords: (3GdeLGejYs